Evaluation of the antibacterial activity of the natural product α-mangostin against Clostridioides difficile - Brice J. Stolz; Ahmed Abouelkhair; Nader S. Abutaleb; Mohamed N. Seleem (PLoS ONE, 2026)
Clostridioides difficile is the leading cause of hospital-associated diarrhea and has remained a consistent threat for older patients and those with comorbidities or vulnerabilities. The high rates of treatment failure and recurrence, along with the decreased effectiveness of first-line treatments highlight the urgent need for the development of new anti- C. difficile agents. α-mangostin is a natural compound isolated from the edible mangosteen fruit pericarps that has known antimicrobial activity. α-mangostin is poorly absorbed from the gastrointestinal tract (GIT), which is ideal for treatment of CDI to accumulate at the site of infection at concentrations capable of clearing C. difficile . We found that α-mangostin was as potent as the standard-of-care vancomycin, inhibiting a diverse panel of C. difficile strains at a concentration range of 0.5–2 µg/mL. It exhibited rapid bactericidal activity, completely clearing C. difficile in vitro within 2 hours, surpassing vancomycin and fidaxomicin. Additionally, α-mangostin’s anti- C. difficile activity was not affected by the high C. difficile inoculum. To further understand its mechanism, we investigated α-mangostin’s membrane disruption activity by assessing the leakage of DNA and ATP post-exposure. α-mangostin resulted in a significant leakage of DNA and ATP indicating that its anti- C. difficile activity is mediated by the bacterial cell membrane disruption. Collectively, these findings demonstrate that α-mangostin possesses desirable characteristics for a promising anti- C. difficile which merits further investigation.